Pemanfaatan Aplikasi i-Waris Sebagai Media Pembelajaran untuk Meningkatkan Pemahaman Siswa terhadap Mata Pelajaran Fiqih al-Mawaris Kelas XII MA Raudhatul Muta'allimin Pacet Kabupaten Bandung - Shaiqh, Neng Moya Sabhana; Nurulhajj, Fadilah Arfan; Aulia, Fitri; Maslani, Maslani (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2025)
Technology not only facilitates access to diverse resources but also allows for personalized learning experiences that cater to individual students' needs. Islamic education, especially in specialized subjects like Fiqh al-Mawaris (Islamic inheritance law), can greatly benefit from these technological advancements. Fiqh al-Mawaris deals with detailed regulations and inheritance shares based on Islamic law, which often involve intricate calculations and precise legal interpretations. Traditional teaching methods, which rely heavily on rote memorization and lectures, may not sufficiently support students in grasping these complexities. The purpose of this study is to examine how the i-Waris application is used as a learning medium and analyze its impact on students' understanding of Fiqh al-Mawaris. This study employed a qualitative research approach with a case study method, aiming to explore in depth the use of the i-Waris application in enhancing students’ understanding of Fiqh al-Mawaris. A qualitative approach was chosen to gain comprehensive insights into the implementation process, students’ experiences, and the contextual dynamics involved in using digital tools for Islamic education. The results of this study demonstrate that the use of the i-Waris application as a learning medium in Grade 12 of MA Raudhatul Muta'allimin Pacet has been shown to improve students' understanding of Fiqh al-Mawaris. The application's interactive features, including step-by-step calculations and scenario simulations, make the learning experience more concrete and understandable for students who previously struggled with the abstract and mathematical aspects of inheritance law.